Aquatic Environments as Vectors for Plant Virus Spread: Challenges and Solutions - Ga-Eun Lee; Seoung-Ah Lee; Min-Jae Kim; Rae-Dong Jeong (Research in Plant Disease)
Plant viruses are transmitted through various pathways, significantly impacting crop productivity and ecosystem health. This paper reviews the major transmission routes of plant viruses and discusses the emerging role of environmental water in virus dissemination. It provides an overview of traditional transmission pathways, including mechanical transmission, insect vectors, contact and seed transmission, soil-mediated transmission, propagation through vegetative organs, and transmission via human and animal activities. Furthermore, this study highlights the occurrence of plant viruses in environmental water and their ecological and agricultural significance. It specifically reviews the transmission mechanisms of environmental water-mediated spread, focusing on the cases of pepper mild mottle virus and tomato brown rugose fruit virus. This review aims to enhance the understanding of the role of environmental water in plant virus research and management strategies, contributing to the development of effective countermeasures.